Stimuli-Responsive and Functionalized Nanosponges: Precision Delivery to the Tumor Microenvironment - Deorankar, Priyanka Suryakant; Munot, Neha Manish; Shirsath, Rahul Bhausaheb; Hinge, Nikhil Pandurang; Bochare, Tejas Pramod; Landage, Akash Balaji; Jain, Kishor Sanchalal (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: Cancer, a primary cause of mortality worldwide, is also challenging to treat because of its complexity and diverse forms. WHO has expressed the need for innovative ways to treat this serious problem. There are more than a hundred types of cancers. The hallmark of cancers is metastasis. Although oncology is evolving, a complete cure seems a distant goal. Major reasons include tumor progression, poor drug solubility, weak tumor-targeting, and off-target effects resulting in systemic toxicity which worsen survival. Purpose: This review aims to critically evaluate the advances in nanosponge-based drug delivery systems for cancer therapy, with emphasis on their potential to overcome the existing therapeutic barriers. The discussion centers on design strategies, mechanisms of action, and their role in tumor targeting thus improving treatment efficacy and safety. Materials and Methods: The review provides an overview of the structure, preparation, and characterization of nanosponges. It specifically examines the challenges posed by the Tumor Microenvironment (TME) and the attempts being made to optimize nanosponges tailored to address such complexities through passive and active targeting strategies like surface modification or stimuli responsiveness. Results: Nanosponges possess a unique porous nature with high loading capacity for both hydrophilic and lipophilic drugs. These carriers enhance site-specificity and bioavailability, thereby effectively reducing the required dose and minimizes adverse off-target effects. Conclusion: Optimized nanosponges tailored for the TME represent a promising frontier in intelligent drug delivery. They serve as a vital tool for advancing precision oncology and improving patient survival.
Keywords: Cancer; Functionalized; Nanosponges; Stimuli responsive; Surface modified